Abrogation of SARS-CoV-2 interaction with host (NRP1) neuropilin-1 receptor through high-affinity marine natural compounds to curtail the infectivity: A structural-dynamics data. (February 2022) - Humayun, Fahad; Khan, Abbas; Ahmad, Sajjad; Yuchen, Wang; Wei, Guoshen; Nizam-Uddin, N.; Hussain, Zahid; Khan, Wajid; Zaman, Nasib; Rizwan, Muhammad; Waseem, Muhammad; Wei, Dong-Qing
Abstract: The evolution of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants around the globe has made the coronavirus disease 2019 (COVID-19) pandemic more worrisome, pressuring the health care system and resulting in an increased mortality rate. Recent studies recognized neuropilin-1 (NRP1) as a key facilitator in the invasion of the new SARS-CoV-2 into the host cell. Therefore, it is considered an imperative drug target for the treatment of COVID-19. Hence, a thorough analysis was needed to understand the impact and to guide new therapeutics development. In this study, we used structural and biomolecular simulation techniques to identify novel marine natural products which could block this receptor and stop the virus entry. We discovered that the binding affinity of CMNPD10175, CMNPD10017, CMNPD10114, CMNPD10115, CMNPD10020. CMNPD10018, CMNPD10153, CMNPD10149 CMNPD10464 and CMNPD10019 were substantial during the virtual screening (VS). We further explored these compounds by analyzing their absorption, distribution, metabolism, and excretion and toxicity (ADMET) properties and structural-dynamics features. Free energy calculations further established that all the compounds exhibit stronger binding energy for NRP1. Consequently, we hypothesized that these compounds might be the best lead candidates for therapeutic interventions hindering virus binding to the host cell. This study provides a strong impetus to develop novel drugs against the SARS-CoV-2 by targeting NRP1. Graphical abstract: Image 1 Highlights: Recent studies identified neuropilin-1 (NRP1) facilitates the entry of the new SARS-CoV-2 into host cells. Therefore, it is deemed as an important drug target for the treatment of COVID-19. We used structural modeling techniques to target NRP1 and stop the virus entry. CMNPD10175, CMNPD10017, CMNPD10114, CMNPD10115, and CMNPD10020 were report as the best compounds. Free energy calculations further established that all the compounds exhibit strong binding energy for NRP1.